2021
DOI: 10.3390/microorganisms9091930
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota-Modulated Metabolomic Profiling Shapes the Etiology and Pathogenesis of Autoimmune Diseases

Abstract: Autoimmunity is a complex and multifaceted process that contributes to widespread functional decline that affects multiple organs and tissues. The pandemic of autoimmune diseases, which are a global health concern, augments in both the prevalence and incidence of autoimmune diseases, including type 1 diabetes, multiple sclerosis, and rheumatoid arthritis. The development of autoimmune diseases is phenotypically associated with gut microbiota-modulated features at the molecular and cellular levels. The etiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 165 publications
(193 reference statements)
0
6
0
Order By: Relevance
“…Although zonulin levels were not included in the present study, they were found to be high in MIS-C cases in a previous study [ 52 ]. In rheumatoid arthritis patients, it was shown that Prevotella activated the TLR-2 receptor of intestinal epithelial cells, stimulated the release of proinflammatory cytokines, such as IL-1β, IL-6, and IL-23, supported the activation of Th17 cells that lead to IL-17 production, and played a role in inflammation [ 53 , 54 ]. In our study, we found that Prevotella at the genus level and Prevotella tannerae were significantly dominant in the intestine at the species level.…”
Section: Discussionmentioning
confidence: 99%
“…Although zonulin levels were not included in the present study, they were found to be high in MIS-C cases in a previous study [ 52 ]. In rheumatoid arthritis patients, it was shown that Prevotella activated the TLR-2 receptor of intestinal epithelial cells, stimulated the release of proinflammatory cytokines, such as IL-1β, IL-6, and IL-23, supported the activation of Th17 cells that lead to IL-17 production, and played a role in inflammation [ 53 , 54 ]. In our study, we found that Prevotella at the genus level and Prevotella tannerae were significantly dominant in the intestine at the species level.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have shown the effect of gut microbiota on the immune system ( de Oliveira et al, 2017 ; Castro Rocha et al, 2020 ), metabolic homeostasis ( Wu et al, 2020 ; Tsai et al, 2021 ), and gastrointestinal integrity ( Owen and Mohamadzadeh, 2013 ; Guerreiro et al, 2018 ). Studies conducted in recent years have suggested that the abnormal immune response of RA may be associated with the imbalance of gut microbiota ( Xu et al, 2020 ; Brandl et al, 2021 ; Li and Wang, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The imbalance of gut microbiota may lead to changes in metabolomic profiling in the human body which accounts for etiology of autoimmune diseases ( Kim et al, 2017 ; Tsai et al, 2021 ; Yang and Cong, 2021 ). Metabolomics, the systematic study of the sets of metabolites in an organism, is an excellent tool to provide further insight or scientific basis into specific pathogeneses as well as the mechanism of actions of botanical medicines ( Marchev et al, 2021 ; Oyenihi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The microbiome, and by extension, the metagenome and metatranscriptome, is variable, depending on many environmental factors, such as anti- and probiotic use, age, diet, environment and physical activity levels. Despite few causal examples, it is widely recognized that changes in the gut microbiota are associated with the onset and progression of non-communicable diseases [reviewed in ( Noce et al, 2019 )], including autoimmune diseases such as multiple sclerosis (MS) and rheumatoid arthritis [RA, ( Tsai et al, 2021 )]. Comprehensive investigations of the microbiome are, by their nature, integrative requiring analyses of the metagenome and metatranscriptome; direct and indirect interactions between the microbiome and the host, and environment-microbe-metabolism interactions ( Kurilshikov et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This means that the metabolome may contribute to our understanding of the developmental basis of disease by refining our ability to assign functional changes to environmental exposures. Recent studies also demonstrate the value of integrating metabolome with microbiome data to profile disease pathogenesis, for example, a recent review of autoimmune disease describes how the microbiome and associated metabolic profile are altered by ‘modern’ lifestyles, which is impacting on inflammatory responses ( Tsai et al, 2021 ). Given that the metabolome itself is the end product of cellular processes, it stands to reason that, like the proteome, it can be indirectly altered by environmentally-induced genomic, epigenetic, structural and microbiotic changes.…”
Section: Introductionmentioning
confidence: 99%